Assessment of patients with a suspected cardioembolic ischemic stroke. A national consensus statement. (1st October 2021) - Aplin, Mark; Andersen, Asger; Brandes, Axel; Dominguez, Helena; Dahl, Jordi S.; Damgaard, Dorte; Iversen, Helle K.; Iversen, Kasper K.; Nielsen, Edith; Risum, Niels; Schmidt, Michael R.; Andersen, Niels H.
Abstract: Objectives: Several cardiovascular, structural, and functional abnormalities have been considered as potential causes of cardioembolic ischemic strokes. Beyond atrial fibrillation, other sources of embolism clearly exist and may warrant urgent action, but they are only a minor part of the many stroke mechanisms and strokes that seem to be of embolic origin remain without a determined source. The associations between stroke and findings like atrial fibrillation, valve calcification, or heart failure are confounded by co-existing risk factors for atherosclerosis and vascular disease. In addition, a patent foramen ovale which is a common abnormality in the general population is mostly an innocent bystander in patients with ischemic stroke. For these reasons, experts from the national Danish societies of cardiology, neurology, stroke, and neuroradiology sought to develop a consensus document to provide national recommendations on how to manage patients with a suspected cardioembolic stroke. Design: Comprehensive literature search and analyses were done by a panel of experts and presented at a consensus meeting. Evidence supporting each subject was vetted by open discussion and statements were adjusted thereafter. Results: The most common sources of embolic stroke were identified, and the statement provides advise on how neurologist can identify cases that need referral, and what is expected by the cardiologist. Conclusions: A primary neurological and neuroradiological assessment is mandatory and neurovascular specialists should manage the initiation of secondary prophylactic treatment. If a cardioembolic stroke is suspected, a dedicated cardiologist experienced in the management of cardioembolism should provide a tailored clinical and echocardiographic assessment.